2020
DOI: 10.1002/ctm2.37
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironmental influences on dendritic cell and T cell function: A focus on clinically relevant immunologic and metabolic checkpoints

Abstract: Cancer immunotherapy is fast becoming one of the most promising means of treating malignant disease. Cancer vaccines, adoptive cell transfer therapies, and immune checkpoint blockade have all shown varying levels of success in the clinical management of several cancer types in recent years. However, despite the clinical benefits often achieved by these regimens, an ongoing problem for many patients is the inherent or acquired resistance of their cancer to immunotherapy. It is now appreciated that dendritic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 360 publications
0
30
0
1
Order By: Relevance
“…The condition of hypoalbuminaemia suggests that the body is in a stage of hypercatabolism, which is prevalent amongst cancer patients, especially those with cachexia. Lymphocytes are important cellular components of the human immune response system that help to fight tumours by inhibiting cancer cell proliferation, invasion and migration [ 30 ]. Saka et al [ 31 ] reported that T cell exhaustion was closely associated with poor prognosis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The condition of hypoalbuminaemia suggests that the body is in a stage of hypercatabolism, which is prevalent amongst cancer patients, especially those with cachexia. Lymphocytes are important cellular components of the human immune response system that help to fight tumours by inhibiting cancer cell proliferation, invasion and migration [ 30 ]. Saka et al [ 31 ] reported that T cell exhaustion was closely associated with poor prognosis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis to explain these findings is the highly immunosuppressive microenvironment of solid tumors, which impedes endogenous T cell function, 28 , 29 , 30 prevents efficient DC activation, 31 and promotes the expansion of immunosuppressive Tregs. 29 , 32 To assess whether these factors might account for the lack of bystander effects we were seeing in our model, we first blocked the inhibitory T cell receptors PD-1 and CTLA-4, given their known ability to inhibit T cell activation, leading to reduced proliferation, cytokine production, and T cell death.…”
Section: Discussionmentioning
confidence: 99%
“… 37 T cell cross-priming—a process in which DCs cross-present exogenous antigens to CD8 T cells, resulting in CD8 T cell activation—is critical in generating endogenous anti-tumor CD8 T cell immunity. 31 Despite the presence of DCs in the TME, it appears that tumor-associated DCs are often defective in their differentiation and activation and are poor stimulators of immune responses. 37 We hypothesized that agents capable of activating DC might thus augment CAR-induced antigen cross-presentation and stimulate endogenous anti-tumor T cells and bystander effects.…”
Section: Discussionmentioning
confidence: 99%
“…The condition of hypoalbuminemia suggests that the body is in a stage of hypercatabolism, which is prevalent among cancer patients, especially those with cachexia. Lymphocytes are important cellular components of the human immune response system that help to ght tumours by inhibiting cancer cell proliferation, invasion and migration 30 . Saka et al 31 reported that the exhaustion of T cells was closely associated with poor prognosis in cancer.…”
Section: Discussionmentioning
confidence: 99%